ANALISIS SUSTAINABILITAS USAHATANI PADI PADA LAHAN GAMBUT DI KABUPATEN KAPUAS - Jhon Wardie; Tri Yuliana Eka Sintha (Fakultas Pertanian dan Bisnis, Universitas Kristen Satya Wacana, 2016)
ABSTRACTThe research aims: (1) to analyze the level of sustainability farming of rice in peatland; and (2) to analyze the level of farmers household income in peat land. The research location determined by purposive sampling in Terusan Karya Village, Bataguh Sub District, Kapuas District. Sampling was done by simple random sampling method by taking 50 farmers household serve as respondent. Data collected in the form of primary and secondary data. To achieve the purpose of the first study were analyzed by scoring sustainability of farming indicators using Likert Scale system. Indicator of farming sustainability is an instrument that includes biophysical and socio-economic aspects used to measure the level of sustainability of farming of rice in peat land. Furthermore, to achieve the purpose of the second study analyzed a simple tabulation to measure the level offarmers household income.Based on the analysis of farming sustainability of rice in peat land turns farming sustainability index by 76.10%, which means that the level of farming sustainability is good category (highly sustainable). The results of the analysis of farmers household income was found that the level of farmer households income of Rp 16,906,614.- which means that the economic situation has been categorized good farmer households.